URGENSI PENDIDIKAN MULTIKULTURAL SEBAGAI UPAYA MENINGKATKAN APRESIASI SISWA TERHADAP KEARIFAN BUDAYA LOKAL - heri cahyono; Iswati Iswati (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2017)
Indonesia is a pluralistic country. Plurality, apart to become a wealth and pride, of course also be a crucial challenge. Multicultural education is an activity in developing human potential that is able to appreciate the wide range of differences and an effort to increase students' appreciation of the wisdom of the local culture. This paper is a literature review encouraging the multicultural education as an educational concept that is very urgent to be implemented in the education unit, given once occurred various problems of conflicts caused by cultural differences. This paper examines how the concept of multicultural education, multicultural education curriculum development in schools, the development of multicultural education in the school curriculum, and the role of multicultural education in improving the students' appreciation of the local cultural wisdom.